LOSS OF MELANOCORTIN-4 RECEPTOR FUNCTION ATTENUATES HPA RESPONSES TO PSYCHOLOGICAL STRESS - Ryan, Karen K. (2014)
The melanocortin 4 receptor (MC4R), well-known for its role in the regulation of energy balance, is widely expressed in stress-regulatory brain regions, including the paraventricular nucleus of the hypothalamus (PVH) and the medial amygdala (MeA). In agreement with this, MC4R has been implicated in hypothalamic-pituitary-adrenocortical axis (HPA) regulation. The present work investigated the role of chronic Mc4r function to modulate basal HPA axis tone and to facilitate acute HPA responses to psychological stress, using a novel rat model with Mc4r loss-of-function. In this study, adult male rats were placed into 3 groups (n=15/group) according to genotype [wild-type (WT); heterozygous mutant (HET); and homozygous mutant (HOM)]. Basal (pre-stress) plasma adrenocorticotropic hormone (ACTH) and corticosterone were measured in the AM and PM, and the HPA axis response to restraint was assessed in the AM. Rats were perfused at 2 hours after restraint to assess the effect of loss of MC4R on stress-induced c-Fos immunolabeling in stress-regulatory brain regions. We find that basal (non-stress) AM and PM plasma ACTH and corticosterone showed a normal diurnal rhythm that was not altered according to genotype. Consistent with this, adrenal and thymus weights were unaffected by genotype. However, the plasma ACTH and corticosterone responses to restraint were significantly reduced by loss of MC4R function. Likewise, stress-induced c-Fos immunolabeling in both PVH and MeA was significantly reduced by loss of Mc4r function. These results support the hypothesis that endogenous MC4R signaling contributes to the HPA axis response to stress. Because MC4R plays a critical role in the regulation of energy balance, the present work suggests that it may also serve as an important communication link between brain metabolic and stress systems.